Effects of Reversal of Water Flow in an Arctic Floodplain River on Fluvial Emissions of CO2 and CH4 - Castro‐Morales, K.; Canning, A.; Körtzinger, A.; Göckede, M.; Küsel, K.; Overholt, W. A.; Wichard, T.; Redlich, S.; Arzberger, S.; Kolle, O.; Zimov, N.; Canning, A.; 2 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; et al. (Journal of Geophysical Research: Biogeosciences, 2022)
When organic matter from thawed permafrost is released, the sources and sinks of greenhouse gases (GHGs), like carbon dioxide (CO2) and methane (CH4) in Arctic rivers will be influenced in the future. However, the temporal variation, environmental controls, and magnitude of the Arctic riverine GHGs are largely unknown. We measured in situ high temporal resolution concentrations of CO2, CH4, and oxygen (O2) in the Ambolikha River in northeast Siberia between late June and early August 2019. During this period, the largely supersaturated riverine CO2 and CH4 concentrations decreased steadily by 90% and 78%, respectively, while the O2 concentrations increased by 22% and were driven by the decreasing water temperature. Estimated gas fluxes indicate that during late June 2019, significant emissions of CO2 and CH4 were sustained, possibly by external terrestrial sources during flooding, or due to lateral exchange with gas‐rich downstream‐flowing water. In July and early August, the river reversed its flow constantly and limited the water exchange at the site. The composition of dissolved organic matter and microbial communities analyzed in discrete samples also revealed a temporal shift. Furthermore, the cumulative total riverine CO2 emissions (36.8 gC‐CO2 m−2) were nearly five times lower than the CO2 uptake at the adjacent floodplain. Emissions of riverine CH4 (0.21 gC‐CH4 m−2) were 16 times lower than the floodplain CH4 emissions. Our study revealed that the hydraulic connectivity with the land in the late freshet, and reversing flow directions in Arctic streams in summer, regulate riverine carbon replenishment and emissions. Plain Language Summary: When the snow and ice melt in the Arctic, then organic matter, carbon dioxide (CO2), and methane (CH4) can be transported from land into rivers. Bacteria or sunlight transform river organic matter, releasing more of those gases. However, little is known about how CO2 and CH4 levels in Arctic rivers change over time or how environmental factors affect them. We measured ...